Physiological changes in blood pressure impact peripheral endothelial function during adolescence. (16th June 2014) - Deda, Livia; Sochett, Etienne B.; Mahmud, Farid H.
Abstract Reactive hyperemia index is a measure of endothelial function used to assess subclinical atherosclerosis. When evaluated in healthy adolescents, significant changes in endothelial function were correlated with advancing age, pubertal status, and blood pressure. Blood pressure was the principal contributor to reactive hyperemia index variability independent of age, lipid profile, body mass index, and/or pubertal status. Interpretation of this peripheral vascular marker should include age and maturational changes in paediatric patients.